Efektivitas Kinerja Karyawan Terhadap Jumlah Delivery Customer Divisi Ppic Di Pt.Hamatetsu Indonesia - Reka Tri Utari (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
This practical work aims to analyze the effectiveness of employee performance on the number of shipments in the PPIC division at PT Hamatetsu Indonesia. The PPIC Division has a crucial role in managing and controlling the flow of production and inventory, which has a direct impact on the number of successful deliveries. This study aims to identify the factors that influence employee performance in the PPIC division and measure their impact on the number of deliveries achieved. The research method used includes data collection through direct observation, interviews with PPIC employees, and analysis of historical data related to performance and number of shipments. The factors studied include the work environment, work motivation and work discipline. The collected data is then statistically analyzed and linked to the number of successful shipments made in a certain period of time. The results of this study are expected to provide a better understanding of the relationship between employee performance in the PPIC division and the number of deliveries. By evaluating the factors that influence employee performance, PT Hamatetsu Indonesia can identify areas that need improvement and implement more effective strategies in optimizing inventory planning and control processes, so as to increase the number of successful deliveries.